INOVASI KEMASAN DAN PELUASAN PEMASARAN PRODUK CINCAU HIJAU KTHR AMANAH - Hariyani, Happy Febrina; Anindyntha, Firdha Aksari (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2021)
Innovation and marketing of a product are prioritized for the progress of a business. KTHR Rukun Amanah produces a product, namely a drink from processed green grass jelly which is one of the advantages with the hope of increasing people's income. However, there are problems faced by KTHR in developing processed green grass jelly products, that are the limited marketing of the product which includes unattractive product packaging and low selling prices. To increase sales and consumer interest in green grass jelly processed drinks, innovation and marketing expansion are needed. The form of innovation carried out here is the design of the brand logo for processing green grass jelly and packaging innovation in the form of bottles to make it more attractive. Furthermore, marketing expansion is carried out by providing access to sell Chao Chendol beverage products to bazaars and also stalls in the campus of the University of Muhammadiyah Malang.Â